Effect of incident wave angle to gap resonance between two fixed barges. (1st August 2022) - Gao, Song; Cong, Peiwen; Teng, Bin
Abstract: With two barges arranged side-by-side subject to wave action, fluid motion within the narrow gap between the two barges can be significant under specific incoming wave frequencies. The phenomenon is commonly referred to as the gap resonance. A linear potential model using a higher-order boundary element method (hobem ) is applied to investigate the effect of the incident wave angle on the resonant fluid motion within the gap for two fixed identical barges with square corners. An adaptive Gaussian method is used with hobem to improve the accuracy for nearly singular integration. The results show that gap resonant peaks at other incident wave angles can be more critical than the beam sea case which is commonly considered the most critical case. Also, the second mode peak value can surpass the first mode peak value at specific conditions and also be considered when during the design phase. Smaller gap width will increase the resonant frequency and peak value but decrease the incident wave angle at which the maximum resonant peak appears. Highlights: HOBEM with an adaptive Gaussian method is used to improve calculation accuracy. The effect of incident angle is discussed. Oblique wave case can be more critical. The effect of gap width on the first two modes of gap resonance is studied.